ANALISIS BIAYA DAN PENDAPATAN AGROINDUSTRI TIWUL INSTAN (STUDI KASUS PADA KELOMPOK WANITA TANI DESA MAJALENGKA KECAMATAN BAWANG BANJARNEGARA) - Sarno - Sarno; Fanny Tri Raditya (Universitas Wahid Hasyim, 2022)
Majalengka Village, Bawang District, Banjarnegara Regency is one of the villages that exists in the development of instant tiwul agroindustry. Tiwul instant is an agro-industry activity that continues to be developed in women's farmer groups. This is supported by an increase in the business development of instant tiwul production and marketing which is quite rapid. Therefore, the intensive development of the tiwul diamond agroindustry must continue to be improved. So far, the members of the women's farmer group do not understand how much production costs have been spent in the production of instant tiwul and how much income they receive. The research objectives are; (a) analyze the production costs and income of instant tiwul agroindustry, and (b) analyze the business feasibility of instant tiwul agroindustry obtained by the members of the women farmer group. The research method used is descriptive analysis method with data collection methods using interviews, observation and literature review. The research targets are members of women's farmer groups who produce instant tiwul. Data analysis methods used are cost and income analysis and business feasibility analysis. The results showed that (1) the production cost of instant tiwul agroindustry carried out by the women farmer group was obtained by an average of Rp. 497,424,-/1 times of production, (b) the amount of revenue obtained from instant tiwul agroindustry was an average of Rp. 1,095. 000,- while the amount of income earned is an average of Rp. 597,576,-/1 times of production, (c) based on business feasibility analysis, the instant tiwul agroindustry is said to be feasible because it obtains R/C Ratio > 1.Keywords: Agroindustry, Analysis, Cost, Income, Instant Tiwul